Critical systems thinking: a practitioner's guide - Jackson, Michael C. (Wiley, 2024)
"Critical systems thinking is a multiperspectival and multimethodologi cal approach to complex problems that takes advantage of the variety o f systems approaches, aware of their different strengths and weaknesse s"–
Keywords: Leadership; System analysis; System theory